Going Places: Unleashing Potential of Viral Marketing - Nida Nuraisha (Jurnal Pendidikan Ilmu Sosial, 2024)
As the tourism industry becomes increasingly competitive, leveraging the power of Viral Marketing has emerged as a transformative energy for destinations and businesses seeking to capture the attention of a global audience. The digital era has significantly impacted the tourism sector, redefining consumer behavior, marketing strategies, and destination management. The research delves into the various aspects of virality, including the impact of user-generated content on social media platforms, online reviews, and how travel decisions are influenced by trends. This article explores the potential of becoming viral that can be used in the tourism industry to increase brand awareness through viral marketing strategies, based on previous literature. The article also discusses the potential challenges and controversies that may arise when promoting tourism virally, offering insights into mitigating negative impacts. Through case studies of successful viral marketing campaigns in the tourism industry, the article identifies patterns and best practices. In conclusion, this article provides a comprehensive guide for tourism professionals, marketers, and stakeholders aiming to unlock the suit of viral potential of their destinations.